Efektifitas alat pengering tipe box gabah padi (Oryza Sativa L.) terhadap tingkat kadar air - Raybian Nur; Muhammad Arsad Al Banjari (TURBO [Tulisan Riset Berbasis Online], 2020)
Barito Kuala is a regency located in South Kalimantan Province. Most people in Barito Kuala Regency are rice farmers. When the rice is harvested, the harvest is traditionally dried by using radiation from the sun. However, the utilization of solar energy cannot always be used for example due to weather effects. Harvested rice has a moisture content of 21-26%. According to the SNI standard (Indonesian National Standard), the maximum moisture content in rice grain to be marketed is 14%. The purpose of this research is to make a tool and measure the level of effectiveness for drying small-scale rice grain. testing is done by taking a portion of rice grain then put into a box type rice grain dryer and compared with drying that utilizes solar energy. The results of the data obtained that every 5 minutes have a difference in the decrease in water content of 2.18% for 20 minutes with an initial water content of 15.3%.Keywords : Rice grain dryer, drying media type, moisture level.